The Influence of Love of Money and Machiavellian Towards Fraud with Faith of Karma Phala as Moderation - I Made Pradnyana Paradila Pradnyana; I Ketut Sujana; Anak Agung Gde Putu Widanaputra; Ni Ketut Rasmini (Jurnal Ilmiah Akuntansi, 2022)
This study aims to analyze the effect of love of money and machiavellian on fraud, as well as to test whether belief in karma phala can weaken this influence. This research was conducted on LPD administrators in Buleleng Regency with a total sample of 213 respondents, which were analyzed by SEM PLS 3.0. The results showed that love of money and machiavellian positively affect fraud. This means that the more the love of money and machiavellian possessed by the LPD management, the higher the tendency to commit fraud. Belief in karma phala can weaken the influence of the love of money and machiavellian on fraud. This means that the attitude of love of money and machiavellian accompanied by the practice of good karma phala can reduce the negative influence of the love of money and machiavellian on fraud.